Optimasi proses nitrasi pada pembuatan nitro selulosa dari serat limbah industri sagu - Purnawan Purnawan (Jurnal Rekayasa Proses, 2010)
Nitrocellulose production from sago fibers was conducted in two steps, i.e. delignification and nitration processes. This work studied the nitration process of sago fiber cellulose. Before nitration, the lignin was removed using the nitrate soda process utilizing nitric acid and sodium hydroxide. The nitration process used an acid solution consisting of nitric acid and sulfuric acid as a catalyst. The process was carried out in a three neck flask equipped with stirrer and temperature control. The effects of reaction time, nitric acid concentration, and sulfuric to nitric acid ratio were investigated. The results showed that the best operating conditions obtained for the reaction time, cellulose to mixed acid ratio and sulfuric to nitric acid ratio were 1.5 hours, 1:20 and 1:4 respectively in which the product yield and nitrogen content were found to be 151.22% and 13.39%. This nitrogen content was close to the theoretical maximum nitrogen content of 14.14%.